2016
DOI: 10.1166/jnn.2016.12650
|View full text |Cite
|
Sign up to set email alerts
|

Applications of TiO<SUB>2</SUB>, ZnO and Ag Nanomaterials to Denim Fabric

Abstract: In previous studies much research has reported the determination of applications of TiO2 (rutile and anatase), ZnO and Ag nanomaterials onto various textile surfaces, but in this study for the first time application to denim fabric and testing of the finished fabric for antimicrobial activities of these nanomaterials was investigated. The presence of nanoparticles on dyed denim fabric surfaces was confirmed by Scanning Electron Microscope (SEM). The nanomaterial-impregnated denim fabric (100% cotton) showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Besides, silver (Ag) nanoparticles are commercially used as a broad-spectrum antibiotic agent and exhibit high performance even at low concentrations (Govindan et al 2012, Chen et al 2014. Since they have a strong antibacterial effect and do not create toxic effects, Ag and Ag compounds can be used on many surfaces and areas where harmful microorganisms are abundant during production or after production (Becenen & Altun 2016). Therefore, in this study, we coated cotton fabric samples with nano-Ag particles using chitosan as a crosslinker and investigated the antibacterial activity of nano-Ag and chitosan together against E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, silver (Ag) nanoparticles are commercially used as a broad-spectrum antibiotic agent and exhibit high performance even at low concentrations (Govindan et al 2012, Chen et al 2014. Since they have a strong antibacterial effect and do not create toxic effects, Ag and Ag compounds can be used on many surfaces and areas where harmful microorganisms are abundant during production or after production (Becenen & Altun 2016). Therefore, in this study, we coated cotton fabric samples with nano-Ag particles using chitosan as a crosslinker and investigated the antibacterial activity of nano-Ag and chitosan together against E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticle average diameter determined by DLS was found to be 98.15 nm ( Figure 2 ). Dense TiO 2 nanoparticles were observed on the fabric, indicating the effect of the chemical composition of the fabric on the nature of the prepared TiO 2 nanoparticles ( 27 , 28 ). The EDX spectra revealed the presence of C, O, and Ti on the surface of cotton fabrics.…”
Section: Resultsmentioning
confidence: 98%
“…Many studies have investigated the UV-blocking capacity of TiO 2 nanoparticles and have shown that the in-situ synthesis of TiO 2 nanoparticles on the fabric surface can lead to UV protection capacity, confirming that in-situ deposition of TiO 2 nanoparticles on fabric can provide good to excellent UV protection (28,29).…”
Section: Upf Valuesmentioning
confidence: 93%
“…Silver nanoparticle with an average diameter of 3.5 ± 0.7 nm can be produced by keratin hydrolysate stabilizer and this can be used for biocompatible antimicrobial coatings on textile materials [65]. Becenen and Altun reported antibacterial property of denim which was treated with ZnO, TiO 2 and Ag nanomaterials [66]. Nano-TiO 2 treated textiles can find application in medical garments to reduce hospital acquired infections [67].…”
Section: A Brief Overview Of Nanomaterials For Textile Applicationsmentioning
confidence: 99%